Bioactive Compounds in some Medicinal Plants from Different Habitats in KSA - Nurah M. Alzamel, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Ethnobotanical and phytochemical studies are beneficial to discover new drugs and exploited as a treatment. The aim of this review is to summarize and document the existing and recent knowledge of ethnomedicine in Kingdom of Saudia Arabia. Methods: For detection of active biological compounds, Phytochemical screening is an important step in traditionally used medicinal plants. Some bioactive chemicals obtained from traditional plants have shown to be capable of reversing antimicrobial resistance and improving antibiotic synergy. Results: Secondary metabolites such as glycosides, terpenoids, tannins, alkaloids, and volatile oil, are responsible for the medicinal characteristics of plants, and their extracts represent a rich reserve of crude pharmaceuticals with therapeutic properties. This study could aid in the development of methods for the long-term usage of medicinal plants, which are among the Kingdom's most endangered natural resources in folk medicine. These plants were found to have therapeutic potential in the treatment of a wide range of ailments, including bone fractures, respiratory tract infections, diseases of skin, rheumatism, asthma, diabetes, fever, constipation, eye and ear problems, colds, measles, bladder and urinary diseases, liver and spleen disorders anemia, epilepsy, typhoid, toothache, hypertension, carcinoma, tuberculosis, stomach problems, and nervous problems. Conclusion: This work provided a solid foundation for future pharmacological research on these plants' extracts.